Biofabrication of Artificial Stem Cell Niches in the Anterior Ocular Segment - Veronica Hidalgo-Alvarez; Hala S. Dhowre; Olivia A. Kingston; Carl M. Sheridan; Hannah J. Levis (Bioengineering, 2021)
The anterior segment of the eye is a complex set of structures that collectively act to maintain the integrity of the globe and direct light towards the posteriorly located retina. The eye is exposed to numerous physical and environmental insults such as infection, UV radiation, physical or chemical injuries. Loss of transparency to the cornea or lens (cataract) and dysfunctional regulation of intra ocular pressure (glaucoma) are leading causes of worldwide blindness. Whilst traditional therapeutic approaches can improve vision, their effect often fails to control the multiple pathological events that lead to long-term vision loss. Regenerative medicine approaches in the eye have already had success with ocular stem cell therapy and ex vivo production of cornea and conjunctival tissue for transplant recovering patients’ vision. However, advancements are required to increase the efficacy of these as well as develop other ocular cell therapies. One of the most important challenges that determines the success of regenerative approaches is the preservation of the stem cell properties during expansion culture in vitro. To achieve this, the environment must provide the physical, chemical and biological factors that ensure the maintenance of their undifferentiated state, as well as their proliferative capacity. This is likely to be accomplished by replicating the natural stem cell niche in vitro. Due to the complex nature of the cell microenvironment, the creation of such artificial niches requires the use of bioengineering techniques which can replicate the physico-chemical properties and the dynamic cell–extracellular matrix interactions that maintain the stem cell phenotype. This review discusses the progress made in the replication of stem cell niches from the anterior ocular segment by using bioengineering approaches and their therapeutic implications.